2023
DOI: 10.58526/jsret.v2i2.167
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Moral Values in The Zootopia Movie

Abstract: This research aimed to identify the types of moral values ​​and describe how these moral values ​​are presented in the Zootopia movie, directed by Byron Howard and Rich Moore. The research design was a qualitative descriptive study; the data sources are the movie itself and the movie script of Zootopia. The SPEAKING Model (setting and scene, participants, ends, act sequence, key, instrumentalities, norms, and genre) by Dell Hymes is used as a framework for assess the conversation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The film, a type of medium, has essential influences in conveying information and conveying messages to people who watch it, and as an audiovisual medium, the film can be used in the process of building emotions, attitudes, and even problemsolving (Mukarromah, 2019). The movie has a moral values that can be a motivation and moral learning process in behavior (Masyitah et al, 2023) Numerous research have been done on the moral lessons found in movies. The first study from Alawiyyah & Oktavi, (2019), that analyzed the moral values in the film Dangerous Minds Movie by John N. Smith.…”
Section: Introductionmentioning
confidence: 99%
“…The film, a type of medium, has essential influences in conveying information and conveying messages to people who watch it, and as an audiovisual medium, the film can be used in the process of building emotions, attitudes, and even problemsolving (Mukarromah, 2019). The movie has a moral values that can be a motivation and moral learning process in behavior (Masyitah et al, 2023) Numerous research have been done on the moral lessons found in movies. The first study from Alawiyyah & Oktavi, (2019), that analyzed the moral values in the film Dangerous Minds Movie by John N. Smith.…”
Section: Introductionmentioning
confidence: 99%